Analog parameters of solid source Zn diffusion InXGa1−XAs nTFETs down to 10 K. (28th October 2016) - Bordallo, C; Martino, J A; Agopian, P G D; Alian, A; Mols, Y; Rooyackers, R; Vandooren, A; Verhulst, A S; Smets, Q; Simoen, E; Claeys, C; Collaert, N
Abstract: The analog parameters of In0.53 Ga0.47 As and In0.7 Ga0.3 As nTFETs with solid state Zn diffused source are investigated from room temperature down to 10 K. The In0.7 Ga0.3 As devices are shown to yield a higher on-state current than the In0.53 Ga0.47 As counterparts, and, consequently, a higher transconductance due to the lower bandgap. At the same time, the In0.7 Ga0.3 As devices present higher output conductance values. The balance between these two factors results in a higher intrinsic voltage gain ( A V ) for In0.7 Ga0.3 As nTFETs at low gate bias and similar A V for both devices at high gate voltage. The transconductance is reduced at low temperature due to the increase of the bandgap, while the output conductance is decreased (improved) upon cooling, which is related to the reduction of the drain dependence of the BTBT generation rate. The temperature influence is more pronounced in the output conductance than in the transconductance, resulting in an increase of the intrinsic voltage gain at low temperatures for both devices and bias.